BUILDING INTELLIGENCE IN THE LEARNING PROCESS IN HIGHER EDUCATION: PHILOSOPHICAL, THEORETICAL, PRACTICAL PARADIGM - Budi, Setia; Zen, Zelhendri; Jasrial; Pratiwi, Rara Ajeng (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The development of student intelligence in higher education often faces challenges because the education system consistently prioritizes cognitive aspects while neglecting other dimensions, such as emotional, social, and creative components. This situation raises the question of how pedagogical strategies can enhance students' intellectual diversity, thereby making the learning process more comprehensive. This study aims to examine students' views on the development of intelligence during the learning process in higher education while providing insights into effective and adaptive learning practices. The method used is a literature review by reviewing scientific articles, research reports, and selected academic literature published between 2013 and 2023. The analysis used a content analysis approach through the stages of synthesis, classification, and data reduction. The results of the study indicate that although learning in higher education is still dominated by a cognitive orientation, emotional, social, and intrapersonal intelligence have been shown to play a significant role in supporting students' academic and personal success. The ideas of Gardner, Vygotsky, and Goleman emphasize the importance of holistic learning that integrates social interaction, emotional regulation, creativity, and ethical and spiritual dimensions. The contribution of this article lies in its efforts to integrate the theories of multiple intelligences, emotional intelligence, and constructivism into a practical framework for developing holistic learning in higher education, as well as providing concrete recommendations for lecturers to expand assessment and learning strategies beyond cognitive biases.